2019
DOI: 10.1137/18m1212082
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Description of Optimally Time-Dependent Modes for Reduced-Order Modeling of Transient Instabilities

Abstract: The optimally time-dependent (OTD) modes form a time-evolving orthonormal basis that captures directions in phase space associated with transient and persistent instabilities. In the original formulation, the OTD modes are described by a set of coupled evolution equations that need to be solved along the trajectory of the system. For many applications where real-time estimation of the OTD modes is important, such as control or filtering, this is an expensive task. Here, we examine the low-dimensional structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…A further step in the understanding of the OTD framework was taken in Blanchard & Sapsis (2019 a ), who consider the link to Gram–Schmidt vectors. They show that on choosing the rotation matrix as the OTD basis vectors become identical to the continuously orthonormalised Gram–Schmidt vectors and the evolution equation for the th OTD basis vector reduces to Apart from the theoretical appeal, this choice of also has advantageous numerical properties since the evolution equations (2.9) are lower triangular (notice the difference in the limit of the sum compared with (2.4)) and can therefore be efficiently solved through forward substitution (Blanchard & Sapsis 2019 a ). The original OTD formulation is not hierarchical in the sense that adding a basis vector requires the recomputation of all vectors.…”
Section: Otd Modesmentioning
confidence: 99%
See 2 more Smart Citations
“…A further step in the understanding of the OTD framework was taken in Blanchard & Sapsis (2019 a ), who consider the link to Gram–Schmidt vectors. They show that on choosing the rotation matrix as the OTD basis vectors become identical to the continuously orthonormalised Gram–Schmidt vectors and the evolution equation for the th OTD basis vector reduces to Apart from the theoretical appeal, this choice of also has advantageous numerical properties since the evolution equations (2.9) are lower triangular (notice the difference in the limit of the sum compared with (2.4)) and can therefore be efficiently solved through forward substitution (Blanchard & Sapsis 2019 a ). The original OTD formulation is not hierarchical in the sense that adding a basis vector requires the recomputation of all vectors.…”
Section: Otd Modesmentioning
confidence: 99%
“…The original OTD formulation is not hierarchical in the sense that adding a basis vector requires the recomputation of all vectors. The Blanchard & Sapsis (2019 a ) formulation overcomes this issue.…”
Section: Otd Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to achieve this is to continuously apply the Gram-Schmidt algorithm to the collection {v i } r i=1 , starting with v 1 and moving down. Blanchard & Sapsis 16 showed that the resulting vectors obeyu…”
Section: A Preliminariesmentioning
confidence: 99%
“…H. Arbaby, D. Sapsis carried out modeling and analysis of systems that have a large number of degrees of freedom, possibly combined with a significant amount of uncertainty in the parameters [1]. A. Blanchard, D. Sapsis predicted transient instability and extreme events in arrogant systems [3]. M. Hadji, J. Kluger, D. Sapsis, A. Slocum substantiated that all this is related to the amount of energy expended and noted that one of the advantages of wave energy is higher predictability and the minimum number of changes [13].…”
Section: Methodsmentioning
confidence: 99%